2008
DOI: 10.1016/j.plaphy.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of a copper-induced anionic peroxidase of sunflower roots

Abstract: Treatment of 14-day-old sunflower seedlings with a toxic amount of copper (50 microM of CuSO(4)) during 5days caused significant increase in peroxidase activity in roots. Qualitative analysis of soluble proteins using native anionic PAGE followed by detection of peroxidase activity with guaïacol as electron donor in the presence of H(2)O(2) revealed five stimulated peroxidases, named A1, A2, A3, A4, and A5. These peroxidases had differential behavior during the period of treatment. A1, A2, A3 and A4 were stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Purified enzyme (25 g) from the homogenous pool fractions (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) were mixed with sample loading buffer and loaded on 12.5% SDS-PAGE under both non-reducing and reducing conditions [20]. The gels were stained with 0.2% Coomassie brilliant blue R-250.…”
Section: Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Purified enzyme (25 g) from the homogenous pool fractions (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) were mixed with sample loading buffer and loaded on 12.5% SDS-PAGE under both non-reducing and reducing conditions [20]. The gels were stained with 0.2% Coomassie brilliant blue R-250.…”
Section: Electrophoresismentioning
confidence: 99%
“…catalyze the formation of harmful free radicals, which causes an oxidative burst and this effect can be improved by anti oxidative systems including peroxidase, e.g. sunflower seeding treated with CuSO 4 [31]. The conformational changes of CCPP under native and denatured GuHCl and urea conditions were studied by fluorescence and circular dichroism.…”
Section: Spectroscopic Studies: Absorbance Fluorescence and Circularmentioning
confidence: 99%
“…Under stress conditions, we observed a stimulation of A2 and A3 in leaves and A1 in roots. In a previous study [20], we have demonstrated that cupric stress enhanced significantly all root isozymes especially A5, this effect is not observed in Al treatment which spectacularly enhanced A1. Thus, it appears that quantitative stimulation of peroxidase activity under metallic stress conditions was not corresponding to the activation of same isoforms.…”
Section: Effect Of Aluminium On Peroxidases Activities and Page Analymentioning
confidence: 58%
“…For sunflower, one of metal hyperaccumulator plants, data on changes in metabolic processes as a result of exposure to Cu, Cd, Fe and Ni reveal a decrease in growth accompanied with significant stimulation of peroxidases activities [11,18,19]. Recently, we have demonstrated that Cu treatment caused the stimulation of a moderately anionic peroxidase (pI=6.7) that was identified and characterised [20]. Here, we examined the peroxidases responses to Al treatment for comparing the Al-induced changes with those caused by other metals in order to fully understand the role of peroxidases in defence mechanisms against metal stress.…”
Section: Introductionmentioning
confidence: 98%
“…4, the activity of purified POD maintained relatively high in the temperature range between 20 and 50C and presented a maximum at 40C. For comparison, it can be stated that the optimum temperature for activity of sunflower roots POD, using coniferyl alcohol as substrate, is also 40C (Jouili et al . 2008).…”
Section: Resultsmentioning
confidence: 99%